Augmented reality interactive photography representation - Yee, Miao Ling. (2012)
This project is based on the study and implementation of the augmented reality (AR) technology being implemented on a photography exhibition. AR technology is a kind of Virtual Reality (VR), which allows a user to not only see the real world around him, but also be able to superimpose virtual objects and visuals onto the real objects in the world around him. For AR technology to be accessible, there are a few very important hardware, aside from the software, such as a central processing unit (CPU), a camera, a display to show the users the results of the AR technology and mircoelectromechanical (MEMS) sensors like an accelerometer. With the proliferation of handheld smart devices and camera phones, the hardware requirements are easily fulfilled, making it both easy and convenient for the general public to experience the AR technology using the devices they already own.